COVID-19 severity and mortality in multiple sclerosis are not associated with immunotherapy: Insights from a nation-wide Austrian registry - Bsteh, Gabriel; Assar, Hamid; Hegen, Harald; Heschl, Bettina; Leutmezer, Fritz; Di Pauli, Franziska; Gradl, Christiane; Traxler, Gerhard; Zulehner, Gudrun; Rommer, Paulus; Wipfler, Peter; Guger, Michael; et al. (PLOS ONE, 2021)
Background The COVID-19 pandemic challenges neurologists in counselling patients with multiple sclerosis (pwMS) regarding their risk by SARS-CoV-2 and in guiding disease-modifying treatment (DMT). Objective To characterize the prevalence and outcome of COVID-19 in pwMS specifically associated with different DMT in a nationwide population-based study. Methods We included patients aged ≥18 years with a confirmed diagnosis of MS and a diagnosis of COVID-19 established between January 1, 2020 and December 31, 2020. We classified COVID-19 course as either mild, severe or fatal. Impact of DMT and specifically immunosuppressants (alemtuzumab, cladribine, fingolimod, ocrelizumab or rituximab) on COVID-19 outcome was determined by multivariable models, adjusted for a-priori-risk. Results Of 126 MS patients with COVID-19 (mean age 43.2 years [SD 13.4], 71% female), 86.5% had a mild course, 9.5% a severe course and 3.2% died from COVID-19. A-priori-risk significantly predicted COVID-19 severity (R2 0.814; p<0.001) and mortality (R2 0.664; p<0.001). Adjusting for this a-priori-risk, neither exposure to any DMT nor exposure to specific immunosuppressive DMT were significantly associated with COVID-19 severity (odds ratio [OR] 1.6; p = 0.667 and OR 1.9; p = 0.426) or mortality (OR 0.5; p = 0.711 and 2.1; 0.233) when compared to no DMT. Conclusions In a population-based MS cohort, COVID-19 outcome was not associated with exposure to DMT and immunosuppressive DMT when accounting for other already known risk factors. This provides reassuring evidence that COVID-19 risk can be individually anticipated in MS and–except for a very small proportion of high-risk patients–treatment decisions should be primarily focused on treating MS rather than the pandemic.